An Assessment of the Exchange Rate Pass-Through in Angola and Nigeria - Lariau, Ana.; El-Said, Moataz; Takebe, Misa. (Washington, D.C. : International Monetary Fund, 2016)
This paper estimates the exchange rate pass-through to consumer price inflation in Angola and Nigeria, with particular emphasis on the changes of the pass-through over time. Even though the two countries share smilar dependence on oil exports, this paper reveals different results. For Angola, the long-run exchange rate pass-through to prices is high, though it has weakened in recent years reflecting the de-dollarization of the economy. In Nigeria, there is no stable long-run relationship between the exchange rate and prices, and changes in the exchange rate do not have a significant pass-through effect on inflation. However, the passthrough effect on core inflation is significant.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet